Blanket guarantee, deposit insurance and restructuring decisions for multinational banks - Mälkönen, Ville; Niinimäki, J.-P. (Journal of Financial Stability, 2012)
This paper examines blanket guarantee, deposit insurance and restructuring decisions with respect to a multinational bank (MNB) using Nash bargaining when the threat of a bank panic motivates countries to make decisions quickly. Failure of the bank would unevenly distribute externalities across countries, influencing the restructuring incentives. In equilibrium, the bank is either liquidated or one of the countries – or both – recapitalizes it. A partition of the recapitalization costs is sensitive to the country-specific benefits and costs from recapitalization, panic and liquidation. The home regulator benefits from the advantage that it is the only entity that can legally liquidate the MNB. Rational expectations regarding the bargaining result affect the incentives to declare a blanket guarantee.